1994
DOI: 10.1111/j.1744-618x.1994.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nursing Diagnosis With Population Groups

Abstract: The authors report findings of a study done to examine the use of nursing diagnosis by community health nurses (n= 15) and students (n= 20) who worked with population groups. Results of the analysis of the open‐ended questionnaires and student assignments indicate that many of the diagnoses, both wellness and deficit, could be classified in relation to the concepts present in published classification systems. Issues raised by the study about the use of nursing diagnosis with population groups include: incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These three studies offer contrasts in their findings in relation to the use and facility of nursing diagnosis as it is applied in the three settings. A fourth study by Neufeld and Harrison (1994) examined the use of nursing diagnoses by community health nurses and nursing students who worked with population groups. Results of this study indicated that many wellness and deficit diagnoses could be classified in relation to the current classification systems.…”
Section: Barriers To the Use Of Nursing Diagnosis Language In Clinicamentioning
confidence: 99%
“…These three studies offer contrasts in their findings in relation to the use and facility of nursing diagnosis as it is applied in the three settings. A fourth study by Neufeld and Harrison (1994) examined the use of nursing diagnoses by community health nurses and nursing students who worked with population groups. Results of this study indicated that many wellness and deficit diagnoses could be classified in relation to the current classification systems.…”
Section: Barriers To the Use Of Nursing Diagnosis Language In Clinicamentioning
confidence: 99%
“…The emerging diagnoses and nursing interventions will differ from those of an individual occupational health nurse concerned with the health of a group of workers in one plant. The nurse concerned with a large geographical jurisdiction might formulate a diagnosis such as the one submitted by a community health nurse in the authors' earlier study (Neufeld & Harrison, 1994):…”
Section: Integrating Nursing Diagnosis For Population Groups Within Cmentioning
confidence: 99%
“…Nursing diagnoses are often confirmed by obtaining mformation from individual members of a group without consideration of group-appropriate methods of data collection (Neufeld & Harrison, 1994). Group-appropriate methods might include random sampling of employees in a large chemical plant for measurement of health status, use of epidemiological data pertinent to the group such as results of a national survey on effects of exposure to chemicals in similar industries, or other systematic methods such as review of accident reports (Neufeld & Harrison, 1991).…”
Section: Confirming Nursing Diagnoses For Population Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid inappropriate community nursing diagnoses, Neufeld and Harrison (1994) recommended using group-appropriate data-collection methods, including random sampling, and using epidemiologic data. Thorough environmental assessment and validation of diagnoses through multiple sources of data were recommended.…”
Section: Community and Environmental Nursing Diagnosesmentioning
confidence: 99%